Initial backscatter occurrence statistics from the CUTLASS HF radars - S. E. Milan; T. K. Yeoman; M. Lester; E. C. Thomas; T. B. Jones (Annales Geophysicae, 1997)
A statistical study of the occurrence of ground and ionospheric backscatter within the fields-of-view of the CUTLASS HF radars, at an operating frequency of 10 MHz, during the first 20 months of operation has been undertaken. The diurnal variation of the occurrence of backscatter and the range at which such backscatter is observed is found to be highly dependent on seasonal changes of the ionospheric electron density in both the E and F region, determined from ionosonde observations. In general, ionospheric backscatter is observed at far ranges during the local day in winter months and at near ranges during the local night in summer months. The Iceland radar observes more near-range E region backscatter than the Finland radar as a consequence of its more zonal look-direction. The dependence of the occurrence of backscatter on geomagnetic activity and radar operating frequency are also investigated. The occurrence of ground and ionospheric backscatter is discussed in terms of HF propagation modes and ionospheric electron densities as well as geophysical processes. A brief assessment of the possible impact of solar cycle variations on the observations is made and frequency management is discussed. Such a study, with its focus on the `instrumental' aspect of backscatter occurrence, is essential for a full interpretation of HF coherent radar observations.